2014
DOI: 10.1016/j.dam.2014.01.017
|View full text |Cite
|
Sign up to set email alerts
|

2-stage robust MILP with continuous recourse variables

Abstract: We solve a linear robust problem with mixed-integer first-stage variables and continuous second stage variables. We consider column wise uncertainty. We first focus on a problem with right hand-side uncertainty which satisfies a "full recourse property" and a specific definition of the uncertainty. We propose a solution based on a generation constraint algorithm. Then we give several generalizations of the approach: for left-hand side uncertainty, for the cases where the "full recourse property" is not satisfi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
2

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 13 publications
0
22
0
2
Order By: Relevance
“…Another popular approach for optimization under uncertainty is two-stage ARO, which hedges against the worst-case uncertainty realization within an uncertainty set. A general twostage ARO problem in its compact form is given as follows [59].…”
Section: Stochastic Robust Optimizationmentioning
confidence: 99%
“…Another popular approach for optimization under uncertainty is two-stage ARO, which hedges against the worst-case uncertainty realization within an uncertainty set. A general twostage ARO problem in its compact form is given as follows [59].…”
Section: Stochastic Robust Optimizationmentioning
confidence: 99%
“…Constraints (22) and (23) ensure that the stock levels are within their limits at the end of each visit. Constrains (24) impose a lower bound on the inventory level at time T for consumption ports, while constrains (25) impose an upper bound on the inventory level at time T for production ports.…”
Section: Inventory Constraintsmentioning
confidence: 99%
“…The model introduced here is an adjustable robust program [22,14,30,49] which features two levels of decisions: rst-stage variables must be xed before the uncertainty is revealed, while adjustable variables can react to account for the uncertainty. Such a concept has also been known as recoverable robustness [38].…”
Section: Mathematical Model For the Robust Formulationmentioning
confidence: 99%
“…From the above motivating example, it can be observed that the data‐driven uncertainty set tends to be tighter than other uncertainty sets when uncertainty data are corrupted. Therefore, the DDANRO approach would generates a less conservative robust solution compared with ARO with Gamma‐uncertainty …”
Section: Data‐driven Adaptive Nested Robust Optimization For High‐dimmentioning
confidence: 99%
“…For the above problem, the optimal value m 6j ð Þ has been proven to be a binary variable. 58 Therefore, we can use Glover's linearization to tackle the bilinear term m 6j ð Þ u t by the substitution g…”
Section: The Tailored Column-and-constraint Generation Algorithmmentioning
confidence: 99%